Грамадска-палітычныя ідэі ў творчасці Aнтонія Cялявы - Bortnik, Ihar (Przegląd Środkowo-Wschodni, 2023)
The article is devoted to the identification of a complex of basic social and political ideas in the work of the Union church figure Antoni Sielawa, using the example of his polemical work „Antelenchus”, published in 1622. It is noted that this work uses a number of key concepts characteristic of the noble political discourse, which was formed in along the lines of the republican tradition (“Rzeczpospolita”, „fatherland”, „law”, „freedom”, „social peace”). The accentuation of excessive freedom in the Polish- Lithuanian Commonwealth in connection with the need to justify the groundlessness of the Orthodox complaints about the violation of their rights and freedoms, which is accompanied by the denial of absolute power and tyranny and the assertion of the priority of peaceful means in the religio-political struggle (dispute project), is notable. When considering the relationship between religious and secular institutions, the autonomy of the church, the inadmissibility of interference in the sphere of its functioning by the state government and secular communities, and the monopoly of the clergy to resolve specifically religious issues are emphasized.